Growth evaluation of largemouth bass raised in aquaculture - first results - Rodrigues, A.M. (2015)
Largemouth bass (Micropterus salmoides) (LB) is a freshwater fish introduced in Portugal (Azores) in the end of XIX Century. It is a very important fish in regional cuisine especially in Ribatejo, Beira Baixa and Alentejo regions. The Sociedade Agrícola Vale de Inguinhos S.A. (SAVI) is the first LB aquaculture industry with permission for production 61.5 tones LB/year. Because in Portugal there are no specific LB comercial feed compound SAVI is now evaluate the growth capacity of wild LB using a commercial feed formulated for seabream and European seabass (protein 47.7%, fat 17.3%). On September 2014 358 juvenile LB (0+ years) were caught from 5 small dams belonging to SAVI. Juvenile were stocked in a circular tank used for compound feed training and evaluate fish growth. On the day zero 57 fish were sampled. The average values were: weight 19.49g (±1.882); length 11.85cm (±0.275); K condition factor 1.170 (±0.081). During the compound feed training period (35 days) the survival rate was 90.2%. A sample of >60 LB was collected every ~30 days. Thirty-five days (n=67) and 67 days (n=80) after the end feed training period, a LB sample were controlled with the following results: weight, 35 days 15.31g (±2.681) and 67 days 20.46g (±5.363) (P<0.05); length, 35 days 11.48cm (±0.708) and 67 days 12.59 cm (±0.770) (P<0.05); K condition factor, 35 days 1.007 (±0.112) and 67 days 1.010 (±0.164) (P>0.05). Water temperature ranged 24.6ºC and 10.0ºC. The first results indicate there was a decrease in weight and K condition factor during feed training period. However, the mortality rate was acceptable. Between 35 to 67 days, largemouth bass weight and length increased significantly. We conclude that commercial compound used at SAVI is appropriate to feed juveniles Micropterus salmoides.